Desa Wisata Bongan Bersih Penyuluhan Lingkungan dan Aksi Gotong Royong Kelompok 23 KKN Nusantara III - Saskara, I Putu Adi; Pradnyani, I Gusti Ayu Dwi; Mahendra, I Gede; Adiari, I Dewa Ayu Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Bongan Bersih Tourism Village is a collaborative initiative between Group 23 KKN Nusantara III students and the Bongan Village community to create a clean, healthy, and sustainable environment. By combining the principles of mutual cooperation, environmental awareness and counseling, this program aims to empower the community in maintaining cleanliness and raising awareness of the importance of maintaining a social, natural and sustainable environment. Through mutual cooperation, groups of KKN students and the village community work together in cleaning activities and sorting waste. This collaborative spirit reflects the values ​​of cooperation and active involvement in creating positive change. In addition, environmental counseling and social action are an integral part of this program. The community is educated about the impact of their actions on the environment and sustainable ways to manage waste and natural resources and also provides attention and care to people in need of assistance. This paper describes the implementation of the Clean Bongan Tourism Village program by Group 23 KKN Nusantara III. Through active community participation and a sympathetic, educational approach, this initiative has succeeded in achieving significant results in maintaining the cleanliness of Bongan village and increasing environmental and social awareness. This program also creates a solid foundation for a society that is more responsive to environmental issues and the common welfare of life.